ACE2 Receptors Finding in Placenta with Intrauterine Fetal COVID-19 Infection: A Meta-Analysis - Tigor Peniel Simanjuntak; Hanny Hadinata Wiranegara; Temmy Hadinata Wiranegara (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2022)
Objective: Association between ACE2 receptors in the placenta and the incidence of intrauterine COVID-19 infection in pregnant women infected with COVID-19 Methods: Systematic review and meta-analysis of placenta in pregnant women with COVID-19 infection, ACE2 receptor in placenta, and RT-PCR of neonates from COVID-19 pregnant women. This study followed the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) protocol. Results: 6 journals meet the inclusion criteria. ACE2 receptors were found in syncytiotrophoblasts 72/72 (100%), cytotrophoblasts 41/72 (56.9%), extravillous trophoblasts 24/72 (33.3%), decidual cells 2/72 (2.7%), villous stromal cells 1/72 (1.3%), and 1/72 stromal cells (1.3%) with the incidence of neonates infected with SARS-CoV-2 from pregnant women with COVID-19 10.5%, odds ratio (OR) between ACE2 receptors and neonates infected with COVID-19 is 1.97 (95%CI 0.05–81.09), the pooled proportion of ACE2 receptor findings in 72 placentas in pregnant women with COVID-19 infection, syncytiotrophoblast 98.3 (95% CI 94.3–99.9), cytotrophoblast 40.3 (95% CI 2.3–88.9), and extravillous trophoblast 35.2 (95% CI 0.2–88.5). Conclusion: Expression of ACE2 receptors is always present in the placenta of pregnant women, and there is an association but non-significant between ACE2 receptors in the placenta and the incidence of COVID-19 intrauterine infection with an odds ratio of 1.97 (95%CI 0.05-81.09).Reseptor ACE2 Pada Plasenta dengan Kejadian Infeksi COVID-19 Intrauterine Pada Fetus: A Meta-AnalysisAbstrakTujuan: Hubungan antara reseptor ACE2 di plasenta dengan angka kejadian infeksi COVID-19 intrauterine pada ibu hamil yang terinfeksi COVID-19. Metode: Tinjauan sistematis dan meta-analisis plasenta pada ibu hamil COVID-19, reseptor ACE2 pada plasenta, dan hasil uji RT-PCR neonatus dari ibu hamil COVID-19. Penelitian ini mengikuti protokol Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA). Hasil: 6 jurnal memenuhi kriteria. Reseptor ACE2 ditemukan di sinsitiotrofoblas 72/72 (100%), 41/72 sitotrofoblas (56.9%), trofoblas ekstravili 24/72 (33.3%), sel desidua 2/72 (2.7%), sel stroma vili 1/72 (1.3%), dan sel stroma 1/72 (1.3%) dengan insidensi neonatus yang terinfeksi SARS-CoV-2 dari ibu hamil dengan COVID-19 sebanyak 10.5%, odds ratio (OR) antara reseptor ACE2 dan neonatus terinfeksi COVID-19 adalah 1.97 (95%CI 0.05–81.09), proporsi gabungan penemuan reseptor ACE2 pada 72 plasenta ibu hamil COVID-19, sintiotrofoblas 98.3 (95%CI 94.3 – 99.9), sitotrofoblas 40.3 (95%CI 2.3 – 88.9), dan trofoblas ekstravili 35.2 (95%CI 0.2 – 88.5). Kesimpulan: Ekspresi reseptor ACE2 selalu ditemukan di plasenta ibu hamil, dan terdapat hubungan yang tidak bermakna antara reseptor ACE2 di plasenta dengan kejadian infeksi intrauterine COVID-19 yaitu odds ratio 1.97 (95%CI 0.05-81.09).Kata kunci : Infeksi COVID-19, Intrauterine, reseptor ACE2 plasenta.